Transport Phenomena in Micro Process Engineering - Kockmann, Norbert. (Heat and Mass Transfer,, 2008)
In this book, the fundamentals of chemical engineering are presented aiming to applications in micro system technology, microfluidics, and transport processes within microstructures. After a general overview on both disciplines and common areas, recent projects are shortly presented. The combination of different disciplines gives new opportunities in microfluidic devices and process intensification, respectively. Special features of the book are: - the state-of-the-art in micro process engineering - a detailed treatment of transport phenomena for engineers - a design methodology from transport effects to economic considerations - a detailed treatment of chemical reaction in continuous flow microstructured reactors - an engineering methodology to treat complex processes. The book addresses researchers and graduate students in the field of chemical engineering, Microsystems engineering, and chemistry.